ANALISIS KEBIJAKAN PENGEMBANGAN BUDIDAYA RUMPUT LAUT GRACILARIA SP DALAM TAMBAK DI KECAMATAN MUARA BADAK - Onna Windah (Universitas 17 Agustus 1945 Samarinda, 2018)
Aquaculture at Muara Badak Subdistrict has been cultivating shrimp and fish. The phenomenon that occurred at recent years ago low productivity of pond due to natural and diseases factors, so farmers switch a policy at cultivation seaweed species Gracilaria sp at ponds.. The aim research to development analysis for cultivation condition of species Gracilaria sp at ponds and reviewing of development policy of seaweed cultivation Gracilaria sp. method combination analysis SWOT and Analytical Hierarchy Process (AHP) used to be set development strategy. The result of alternative strategi earn value of strategy I (SO) 7,044, the strategy II (WO) 6,109, the strategy III (ST) 5,522 and the strategy IV (WT) 4,587. the AHP's strategy of main priority 1 (A2) 0.309, priority alternative 2 (A3) 0.208, priority alternative 3 (A1) 0.168, priority alternative 4 (A5) 0.121, priority alternative 5 (A6) 0.080, priority alternative 6 (A8) 0.054, priority alternative 7 (A7) 0.037 and priority alternative 8 (A4) 0.025.